Animal contact in public settings-risk awareness of enteric pathogens and hand hygiene behaviors. (September 2018) - Xu, Wenqing; Cater, Melissa; Gravois, Rebecca; Navarre, Christine; Coulon, Diana; Djebbi-Simmons, Dorra; Wong, Austin
Abstract: Contact with animals in public settings can provide education and entertainment opportunities for both adults and children. However, outbreaks have been associated with human-animal interactions at state, region or county fairs, petting zoos, educational farms, etc. Those outbreaks not only raised a public health concern, but also had substantial medical, legal, and economic impacts. In this study, we assessed the risk awareness of enteric pathogens associated with animal contact in public settings. Participants were asked whether they recognize the risk of spreading enteric pathogens through specific animal contact behaviors such as petting animals with hands or eating around farm animals. The results showed that the self-reported risk awareness was 4.0 ± 1.2 out of a total score of 6, which indicated a poor risk awareness. We also assessed the hand hygiene behaviors including hand washing and hand sanitizer application. Most participants (n = 177, 78.0%) reported that they wash their hands immediately after contact with animals. Logistic regression results showed that risk awareness associated with animal contact was a reliable predictor of hand washing behaviors. Findings from this study serve as a needs assessment for future education to reduce risk of spreading enteric pathogens during animal contact in public settings. Highlights: Infectious disease outbreaks were associated with animal contact. Participants showed poor risk awareness (4.0 out of 6.0) during animal contact. Seventy eight percent of participants reported immediately handwashing after contact. Awareness of risks was a reliable predictor of hand washing behaviors.